The chemokine fractalkine (CX3CL1) attenuates H(2)O(2)-induced demyelination in cerebellar slices - O’Sullivan, Sinead A. (J Neuroinflammation, 2017)
BACKGROUND: Fractalkine/CX3CR1 signalling has been implicated in many neurodegenerative and neurological diseases of the central nervous system (CNS). This signalling pathway plays an important role in regulating reactive oxygen species (ROS), as well as itself being altered in conditions of oxidative stress. Here, we investigated the effects of recombinant fractalkine (rCX3CL1) in models of hydrogen peroxide (H(2)O(2))-induced demyelination and astrocyte toxicity, within organotypic cerebellar slice cultures. METHODS: Organotypic cerebellar slice cultures were generated from postnatal day 10 C57BL/6J mice to assess myelination. Immunohistochemistry was used to measure the degree of myelination. Fluorescent images were obtained using a leica SP8 confocal microscope and data analysed using ImageJ software. RESULTS: We show here, for the first time, that rCX3CL1 significantly attenuated bolus H(2)O(2)-induced demyelination as measured by expression of myelin basic protein (MBP) and attenuated reduced vimentin expression. Using the GOX-CAT system to continuously generate low levels of H(2)O(2) and induce demyelination, we observed similar protective effects of rCX3CL1 on MBP and MOG fluorescence, although in this model, the decrease in vimentin expression was not altered. CONCLUSIONS: This data indicates possible protective effects of fractalkine signalling in oxidative stress-induced demyelination in the central nervous system. This opens up the possibility of fractalkine receptor (CX3CR1) modulation as a potential new target for protecting against oxidative stress-induced demyelination in both inflammatory and non-inflammatory nervous system disorders.